Understanding the Role of Cesium and Rubidium Additives in Perovskite Solar Cells: Trap States, Charge Transport, and Recombination. Issue 16 (26th January 2018) - Hu, Yinghong; Hutter, Eline M.; Rieder, Philipp; Grill, Irene; Hanisch, Jonas; Aygüler, Meltem F.; Hufnagel, Alexander G.; Handloser, Matthias; Bein, Thomas; Hartschuh, Achim; Tvingstedt, Kristofer; Dyakonov, Vladimir; et al.
Abstract: Adding cesium (Cs) and rubidium (Rb) cations to FA0.83 MA0.17 Pb(I0.83 Br0.17 )3 hybrid lead halide perovskites results in a remarkable improvement in solar cell performance, but the origin of the enhancement has not been fully understood yet. In this work, time‐of‐flight, time‐resolved microwave conductivity, and thermally stimulated current measurements are performed to elucidate the impact of the inorganic cation additives on the trap landscape and charge transport properties within perovskite solar cells. These complementary techniques allow for the assessment of both local features within the perovskite crystals and macroscopic properties of films and full devices. Strikingly, Cs‐incorporation is shown to reduce the trap density and charge recombination rates in the perovskite layer. This is consistent with the significant improvements in the open‐circuit voltage and fill factor of Cs‐containing devices. By comparison, Rb‐addition results in an increased charge carrier mobility, which is accompanied by a minor increase in device efficiency and reduced current–voltage hysteresis. By mixing Cs and Rb in quadruple cation (Cs‐Rb‐FA‐MA) perovskites, the advantages of both inorganic cations can be combined. This study provides valuable insights into the role of these additives in multiple‐cation perovskite solar cells, which are essential for the design of high‐performance devices. Abstract : Time‐resolved microwave conductivity, time‐of‐flight, and thermally stimulated current measurements reveal that Cs reduces the trap density in hybrid lead halide perovskites. Rb additives enhance the charge carrier mobility, but show minor effects on the trap landscape. The increase in open‐circuit voltage in multiple‐cation perovskite solar cells can be related to a reduced trap density through Cs‐incorporation.